Pengaruh Pemupukan Ulang Kotoran Ayam Kering Terhadap Populasi Cacing Tubifex tubifex [The Effect Of Remanuring Dry Chicken Manure In Tubifex tubifex Population] - Kustiawan Tri Pursetyo; Woro Hastuti Satyantini; A. Shofy Mubarak (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Tubifex tubifex is one kind of natural food for fish larva. This worm has an important role because it can support the fish growth faster than another natural food like Daphnia sp. or Moina sp. It is caused by its has high nutrition. Dry chicken manure can be used for manuring worm media because it have high organic matter. The purpose of this research was to know the effect of remanuring dry chicken manure to the population of Tubifex tubifex and to know the remanuring of dry chicken manure which is gives high population of Tubifex tubifex. The method used was experimental method. Completely Randomize Design was used in this research with 4 dose manuring treatments and 4 replication : PI (dose 0,08 g/cm2/l days), P2 (dose 0,4 g/cm2/5 days), P3 (dose 0,8 g/cm2/10 days) dan P4 (dose 1,2 g/cm2/15 days). The analysis result showed that the treatment of PI (dose 0,08 g/cm2/l day), manuring of dry chicken manure could give the highest population of Tubifex tubifex was 505 individuals reached at days20. At days-30 there was decreasing total number population so that the harvesting of Tubifex tubifex could be done at days-20. The water quality during this research were pH 6,4 - 7; DO 1,2 - 3,8 mg/1; water temperature 28 - 30 °C and ammonia 0,06 mg/1. The water quality was in optimum condition for Tubifex tubifex growth.